A general map of North America drawn from the best surveys. - Scoles, John, 1772?-1853. (Smith, Reid, & Wayland, 1795)
Map shows major settlements and interior rivers for the fifteen United States, French Louisiana, New Spain, and the West Indies; coastline detail for Atlantic, Pacific, and Gulf coasts. Includes "References to the United States," a key to the names of the state. Scale not given.